2019
DOI: 10.1039/c9tc00625g
|View full text |Cite
|
Sign up to set email alerts
|

Few-layer ReS2(1−x)Se2x nanoflakes for noise-like pulse generation in a mode-locked ytterbium-doped fiber laser

Abstract: We investigated the ternary ReS2(1−x)Se2x alloys and fabricated few-layer ReS1.02Se0.98 nanoflakes to realize passive Q-switch and noise-like pulses operating at 1 μm wavelength.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…In this work, we employed ternary ReS 32,33) Besides, the photon energy in 2 μm is smaller than other shorter wavelength, which is conducive to the improvement of the tolerance of average power.…”
mentioning
confidence: 99%
“…In this work, we employed ternary ReS 32,33) Besides, the photon energy in 2 μm is smaller than other shorter wavelength, which is conducive to the improvement of the tolerance of average power.…”
mentioning
confidence: 99%
“…It is universally known that the generation of all-normal dissipative solitons (DS) with bell-shape spectra and large chirp is the result of the balance of gain, loss, spectral filtering, nonlinear effects and dispersion in the laser cavity. In 2012, Li et al demonstrated a self-started modelocked YDF laser with GO at different cavity length (Figure 8a-c (Figure 8g-i) [139]. Here, many typical low dimension materials such as graphene, TMD, TIs and so on, were applied for the ultrashort pulse generation in the 1 μm region and have been presented in Table 1.…”
Section: μM Wavelength Mode-locked Fiber Lasersmentioning
confidence: 99%
“…(g) Diagram of the mode-locked fiber setup based on ReS 1.02 Se 0.98 , (h) optical spectrum and (i) output pulse train (inset: magnified autocorrelation curve of the NLPs). (a-c) [137], (d-f )[138], (gi)[139].…”
mentioning
confidence: 99%
“…In all-normal dispersion (ANDi) ytterbium doped fiber (YDF) laser oscillators NLPs have been generated using nonlinear polarization rotation (NPR) based SA in a ring cavity [19]. Customized material based SAs such as WS 2 [20], ReS 2(1−x) Se 2x nanoflakes [21] etc have also been shown to generate NLPs in YDF oscillators. In general, in an ANDi oscillator a bandpass filter (BPF) is implemented for pulse stabilization [22,23].…”
Section: Introductionmentioning
confidence: 99%